Crescimento e rendimentos de milho cultivado com controle de plantas daninhas via consorciação com gliricídia - Araújo Junior, Bernardo Bezerra de (Universidade Federal Rural do Semi-Árido, 2010)
Several alternatives have been developed in order to reduce the effect of competition by weeds on crops. Based on this, was carried a study to evaluate the growth and yields of grain and green ears of corn in response to the method of weed control. The experimental was a randomized block design in split plot with eight replications. The plots were to control of weeds without hoeing, intercropped with Gliricidia (Gliricidia sepium) and with hoeings (at 25 and 45 days after planting), and the subplot was at the timing of sampling of plants to 27; 34; 41; 48; 56; 63; 70; 82; 91 and 98 days after planting. At the planting of corn, 25 gliricidia seeds were planted per square meter (m²) between the rows of intercropped corn plots. The highest values for leaf area, dry matter of leaf and dry matter of the above-ground part as well as the maximum absolute growth rates were observed in treatment with hoeings. The treatment intercropped presented intermediate values between those obtained to the treatments with and without hoeings and the latter showed the lowest values. In the green corn there was no treatment effect to the total number of ears, but to the total weight of ears in husk, the weight and number of husked ears and the number and weight of marketable husked ears were observated significant effects. The highest values were observed in the treatment with hoeings and the lowest in the treatment without hoeing. In the intercropped treatment the losses were reduced by 70% to weight of marketable husked ears in relation to cultivation without hoeings. It was not observed any significant effects for weight of 100 grains, however for number of ears, number of grains per ear and yield, the highest values were to the treatment with hoeings and the lowest were observated in the treatment without hoeing. In the intercropped treatment with gliricidia, intermediate values were observed, with losses reduced by up to 39% for number of spikes in relation to treatment without hoeing.
Growth and yield of corn grown with weed control via intercropping with Gliricidia
Keywords: Zea mays; Gliricidia sepium; Análise de crescimento; Milho verde; Zea mays; Gliricidia sepium; Growth analysis; Green corn; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA